A PROPOSED CYBERBYSTANDER INTERVENTION MODEL FOR THE 21ST CENTURY - Dillon, Kelly (AoIR Selected Papers of Internet Research, 2015)
On the Internet, no one may know you’re a dog, but this also means no one knows you could play fetch or run for help. While we are more connected to known and unknown others more than ever, we can still feel quite alone and separated, especially when in need. An increasing reliance on computer-mediated communication to work and socialize has lead to a rise in hostile and negative communication. The deindividuating nature of the Internet makes intervening in perceived cyberemergencies such as cyberharassment, cyberbullying, and cyberthreats difficult, but not impossible. Individuals uninvolved in incidents are considered cyberbystanders, and a new model is necessary to test the boundary conditions of cyberbystander intervention. The rapid changes in technology, the near constant increase in access, and the moving target of determining who is accessing what through what means and to what degree they are aware of its effects make determining action difficult and daunting. Specific communication models and theories offer commentary on how offline models of bystander intervention may operate online. A more comprehensive model of cyberbystander intervention is proposed.